Approximation characteristics of the classes $B_{p,θ}^{Ω}$ of periodic functions of many variables - Stasyuk, S. A.; Fedunyk, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We obtain exact order estimates for the approximation of the classes $B_{p,θ}^{Ω}$ of periodic functions of many variables in the space $L_q$ by using operators of orthogonal projection and linear operators satisfying certain conditions.